Higher Education: emotions and the teaching-learning process (Práxis Educativa, 2021)
This study presents the results of a master's degree research that investigated the reasons that led undergraduate students to seek psychological care and established relationships between these reasons and the teaching-learning process. The data were obtained through a questionnaire, applied to 30 students aged 18 years or older, on a federal university campus in the interior of the state of Paraná, Brazil. The investigation was qualitative and exploratory. The data were systematized and analyzed using Bardin's content analysis, based on Cultural-Historical Psychology and the Bakhtinian perspective of language. The results highlighted different reasons, which were organized into four thematic categories: changes in living conditions, academic adaptation/professional choice, impact/emotional reactions, and the teaching-learning process. The reasons for seeking psychological assistance showed a relationship with the emotional states presented by the students and indicated a significant impact on the learning condition.Keywords: Emotions. Higher Education. Teaching-Learning.